Management of the sustainable development of machine-building enterprises: a sustainable development space approach - Latysheva, O. V.; Rovenska, V. V.; Smyrnova, I. I.; Nitsenko, V.; Balezentis, T.; Streimikiene, D.; Латишева, О. В.; Ровенська, В. В.; Смирнова, І. І. (Publisher Emerald Publishing Limited, 2021)
The paper embarks on the development of theory and methodology for managing the sustainabledevelopment of machine-building enterprises through the use of quantitative modeling tools. The articleproposes an algorithm for estimating the position of an enterprise in its competitive space for sustainabledevelopment.Design/methodology/approach–The three dimensions of sustainability (social, economic, environmental)are represented by the equations based on the multiple criteria of sustainability. The three-dimensional space isconstructed and the effects of managerial decisions can be quantified in terms of the latter space.Findings–The proposed model is applied in the case of Ukrainian machinery construction company. Theeffects of introduction of the environmentally friendly business strategy are assessed in the three-dimensionalsustainability space. The changes in the level of sustainability can be estimated based on the projected changesin the criteria of sustainability.Originality/value–The proposed methodology combines expert knowledge, empirical data and quantitativemethods in order to quantify the level of sustainability of enterprises. The model can be extended to includeadditional dimensions and applied to different empirical cases.
Keywords: Sustainable development; Three-dimensional space; Environmental component; Economicsteadiness; Social responsibility; Ecological activity